2012
DOI: 10.1097/ncm.0b013e318253f029
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing

Abstract: The design and implementation of a comprehensive and effective case management plan of care is facilitated by motivational interviewing, whereby professional case managers establish collaborative, respectful, trusting and individualized relationships with clients. Using the specific principles and techniques of motivational interviewing, case managers take a holistic approach to care to address a client's willingness and ability to change; addressing self-confidence and other emotional triggers that affect cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…We chose to MI as the tool to deliver the intervention, a technique successfully implemented health behavior change studies [30]. MI is based on the clinical principles of (1) expressing empathy, understanding, and acceptance, including understanding that ambivalence is normal; (2) identifying discrepancies between current behavior and important goals and facilitating the participant to present rationale for change, rather than using direct persuasion techniques; (3) allowing the participant to be resistant to change, so resistance can be explored and the participant can resolve resistance; and (4) supporting self-efficacy for change by identifying the participant’s strengths, encouraging his/her ability for change, and affirming successes and achievements [30, 31]. While SDT and MI were developed independently, there are considerable similarities [29, 32] and MI is a common approach for implementing SDT interventions [29, 32].…”
Section: Methodsmentioning
confidence: 99%
“…We chose to MI as the tool to deliver the intervention, a technique successfully implemented health behavior change studies [30]. MI is based on the clinical principles of (1) expressing empathy, understanding, and acceptance, including understanding that ambivalence is normal; (2) identifying discrepancies between current behavior and important goals and facilitating the participant to present rationale for change, rather than using direct persuasion techniques; (3) allowing the participant to be resistant to change, so resistance can be explored and the participant can resolve resistance; and (4) supporting self-efficacy for change by identifying the participant’s strengths, encouraging his/her ability for change, and affirming successes and achievements [30, 31]. While SDT and MI were developed independently, there are considerable similarities [29, 32] and MI is a common approach for implementing SDT interventions [29, 32].…”
Section: Methodsmentioning
confidence: 99%
“…Strong evidence indicated that by setting specific and realistic goals, discussing problem-solving skills to remove barriers, and providing some levels of supervision, depressed patients would be more likely to adopt the proposed behavioral changes [57]. Moreover, techniques such as motivational interviewing are likely to be effective in engaging depressed patients to move toward desirable lifestyle changes [58][59][60]. In the current treatment protocol, we have integrated elements of motivational interviewing and SMART goal-setting in each treatment session.…”
Section: Discussionmentioning
confidence: 99%
“…As front-line team members, community health workers have been found to be effective at providing social supports for patients [12]. A heavy emphasis on the use of motivational interviewing techniques by all care coordination team members to assist patients through challenging tasks that require high levels of executive function could also be a helpful tool [19]. …”
Section: Discussionmentioning
confidence: 99%